Effect of different drying treatments on the concentration of nutrient content and functional properties of black turmeric (Curcuma caesia) - Datta, Sritama; Kumari, P Vasantha (Journal of Postharvest Technology, 2024)
Curcuma caesia is the blackish-blue variant of yellow turmeric. Plant rhizome is popularly used by  tribal communities due to its medicinal properties, still it remains unknown and underutilized by  majority of population. The study aims to analyse the effect of different drying treatments (sun  drying, hot-air-oven drying, and microwave drying) on nutrient composition and phytochemical  content of black turmeric. Results showed that the Hot-air-oven Dried sample had significantly  (p
Keywords: Black turmeric; phytochemical components; medicinal benefits,; hot-air-oven drying.